Innovation and Carbon Emissions: A Southeast Asian Perspective - Hardi, Irsan; Çoban, Mustafa Necati; Fumey, Michael Provide (Heca Sentra Analitika, 2025)
In an era where sustainable development is paramount, understanding the relationship between innovation and environmental impact has become increasingly critical. As Southeast Asian (SEA) economies strive to transition toward more knowledge-based and technology-driven growth, it is crucial to assess whether innovation fosters sustainability or exacerbates environmental degradation. This study examines the impact of the innovation ecosystem on CO2 emissions in selected SEA countries, utilizing various metrics from the Global Innovation Index (GII) grouped into five categories: institutions, human capital and research, infrastructure, market sophistication, and creative outputs. By employing Generalized Linear Models (GLMs) and conducting robustness checks with Robust Least Squares (RLS), the study reveals that all GII categories significantly impact CO2 emissions. However, the findings indicate that this impact is positive, meaning that the innovation landscape in SEA continues to contribute to rising CO2 emissions. The country-specific analysis also confirms that most of the GII categories are still not environmentally friendly. This evidence underscores the need for policymakers in SEA countries to prioritize the development of environmentally sustainable innovation frameworks that promote the adoption of inclusive green technologies and practices to mitigate the adverse effects of innovation on CO2 emissions.